Numerical and Experimental Investigation of a Supersonic Flow Field around Solid Fuel on an Inclined Flat Plate. (7th May 2009) - Hsu, Uzu-Kuei
Abstract : This research adopts a shock tube 16 meters long and with a 9 cm bore to create a supersonic, high-temperature, and high-pressure flowfield to observe the gasification and ignition of HTPB solid fuel under different environments. Also, full-scale 3D numerical simulation is executed to enhance the comprehension of this complex phenomenon. The CFD (Computational Fluid Dynamics) code is based on the control volume method and the pre-conditioning method for solving the Navier-Stokes equations to simulate the compressible and incompressible coupling problem. In the tests, a HTPB slab is placed in the windowed-test section. Various test conditions generate different supersonic Mach numbers and environmental temperatures. In addition, the incident angles of the HTPB slab were changed relative to the incoming shock wave. Results show that as the Mach number around the slab section exceeded 1.25, the flowfield temperature achieved 1100 K, which is higher than the HTPB gasification temperature (930 K~ 1090 K). Then, gasification occurred and a short-period ignition could be observed. In particular, when the slab angle was7 ∘, the phenomenon became more visible. This is due to the flow field temperature increase when the slab angle was at7 ∘ .